Islamic Law Review on Polygamy: Gender Justice and Human Rights - Dewi Ulfa Lailatul Fitria; Rona Merita (Universitas Muhammadiyah Palu, 2023)
This article examines the intersection of polygamy, gender justice, and human rights within the framework of Islamic law. The primary objective is to analyze how traditional Islamic practices regarding polygamy can be reconciled with contemporary human rights principles, particularly focusing on the implications for women's rights. Utilizing a qualitative approach, the study reviews relevant Islamic legal texts alongside international human rights conventions, such as the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW). The findings indicate that while polygamy is permissible in Islam under specific conditions—primarily the requirement of justice among wives—its practical application often leads to violations of women's rights and gender inequality. Furthermore, the research highlights the necessity for reform in legal frameworks governing polygamy to ensure alignment with human rights standards. The significance of this study lies in its potential to inform policymakers and scholars about the need for a balanced approach that respects both Islamic teachings and modern human rights norms, ultimately promoting gender justice within Muslim societies.